2016
DOI: 10.1158/0008-5472.can-15-1233
|View full text |Cite
|
Sign up to set email alerts
|

Penfluridol: An Antipsychotic Agent Suppresses Metastatic Tumor Growth in Triple-Negative Breast Cancer by Inhibiting Integrin Signaling Axis

Abstract: Metastasis of breast cancer, especially to the brain, is the major cause of mortality. The inability of anti-cancer agents to cross the blood-brain-barrier represents a critical challenge for successful treatment. In the current study, we investigated the anti-metastatic potential of penfluridol (PF), an antipsychotic drug frequently prescribed for schizophrenia with anti-cancer activity. We show that PF induced apoptosis and reduced the survival of several metastatic triple negative breast cancer (TNBC) cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 41 publications
7
80
0
Order By: Relevance
“…Many of the effects observed in breast and other cancer cell lines treated with penfluridol and other phenothiazine derivatives are similar to that observed after knockdown of Sp transcription factors Sp1, Sp3 or Sp4 or after treatment with agents that target Sp TFs (1018). For example, knockdown of Sp1, Sp3 or Sp4 individually or combined decreased proliferation and migration/invasion of breast (MDA-MB-231 and SKBR3) and other cancer cell lines (12) and similar results were observed for drugs that repress Sp TF expression (1318).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Many of the effects observed in breast and other cancer cell lines treated with penfluridol and other phenothiazine derivatives are similar to that observed after knockdown of Sp transcription factors Sp1, Sp3 or Sp4 or after treatment with agents that target Sp TFs (1018). For example, knockdown of Sp1, Sp3 or Sp4 individually or combined decreased proliferation and migration/invasion of breast (MDA-MB-231 and SKBR3) and other cancer cell lines (12) and similar results were observed for drugs that repress Sp TF expression (1318).…”
Section: Introductionmentioning
confidence: 64%
“…Phenothiazine-derived antipsychotic drugs such as thioridazine and chlorpromazine exhibit anticarcinogenic activity in several different cancer cell lines (39). More recent studies have demonstrated that penfluridol, another antipsychotic drug, also inhibits breast and pancreatic cancer cell growth (9,10). For example, in pancreatic cancer a series of phenothiazene analogs induced apoptosis and inhibited clonogenic growth and colony formation, and more detailed studies with penfluridol indicated that induction of protein phosphatase 2A (PP2A) was a key effect of this compound (9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we have established the anti-cancer effects of penfluridol against breast cancer and its metastasis to brain through inhibition of integrin signaling, whereas Wu et al 24 observed dysregulation of cholesterol homeostasis by penfluridol in breast cancer. 17 ER plays critical role in synthesis and secretion of transmembrane and secretary proteins. The adaptive response to ER stress is unfolded protein response (UPR).…”
Section: Discussionmentioning
confidence: 99%